Direct Synthesis of 2-(4-Hydroxyphenoxy)benzamide Derivatives from 2-Aryloxybenzamide via PhIO-Mediated Oxidation Reaction - Zhenhua Shang; Dechen Jiao; Haoran Cheng; Daowei Huang (Molecules)
The 2-(4-hydroxyphenoxy)benzamide scaffold is frequently found in a variety of bioactive compounds, displaying a broad spectrum of properties, such as antibacterial and antitumor effects. In this study, we developed a new method for synthesizing 2-(4-hydroxyphenoxy)benzamide derivatives from 2-aryloxybenzamide via a PhIO-mediated oxidation reaction. The optimal reaction conditions were established as follows: TFA was used as the solvent, PhIO served as the oxidant with a substrate-to-oxidant ratio of 1:2, and the reaction was conducted at room temperature. This method, characterized by mild reaction conditions, broad applicability, and a metal-free nature, considerably improves the accessibility of 2-(4-hydroxyphenoxy)benzamide derivatives, which have been challenging to prepare using previously reported methods.